SIGN INFLUENCE OF SAMSUNG 28 AND XIAOMI 5X ADS: SEMIOTIC APPROACH - Ahmad Guntur Saputra; Nenden Rikma Dewi (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
Product advertisements are used to introduce finishing products to the public. The purpose of advertising products is to achieve the sales goal. Currently, Xiomi and Sumsung ads, for example, are heavily published in cyberspace for the same reason. Regularly, they promote their technological advancements on smartphones in this space. In order to convey messages, they exploit icons, symbols and allegory – parts of semiology elements. This study aims to describe signified and signifier constructing linguistic forms of smartphone ads to deliver messages. Qualitative method was used to answer research question – how semiology elements present messages intended – and to describe the phenomena comprehensively. The result shows that elements of semiology functions as mental representation, argued being capable of giving significant impact of sales number of smartphones. Linguistic forms, specifically semiology of elements contribute to deliver messages effectively.